2005
DOI: 10.1191/1078155205jp147oa
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of syringe plungers during the sampling of cyclophosphamide solutions

Abstract: The presence of cytotoxic agents in the urine of operators and in their environment has been demonstrated. The pharmacokinetics of the urinary elimination of cyclophosphamide suggests that these drugs are absorbed cutaneously during handling. In the framework of a more general study on the contamination of hospital environment, the present study addresses the possible presence of cytotoxic agents on the plungers of syringes. The report is based on results indicating that the bacterial contamination of a plunge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…We had little preliminary data to determine the study's sample size; therefore, an assumption of 11 syringes was made based on previous studies. 3,4 The results confirmed the assumption and show that the average contamination level for the BD Õ plungers was ¼ 1622 ng with a variant, 2 ¼ 331 ng 2 . Assuming a normal distribution, CP $ N(, 2 ), the average contamination level on the BD plunger was greater than 1228 ng, with a confidence level of 95%.…”
Section: Statistical Assessmentsupporting
confidence: 57%
See 1 more Smart Citation
“…We had little preliminary data to determine the study's sample size; therefore, an assumption of 11 syringes was made based on previous studies. 3,4 The results confirmed the assumption and show that the average contamination level for the BD Õ plungers was ¼ 1622 ng with a variant, 2 ¼ 331 ng 2 . Assuming a normal distribution, CP $ N(, 2 ), the average contamination level on the BD plunger was greater than 1228 ng, with a confidence level of 95%.…”
Section: Statistical Assessmentsupporting
confidence: 57%
“…Favier et al, 3 in a peer-reviewed study, examined the potential for syringe plunger contamination during routine drug preparations at hospital pharmacies.…”
Section: Introductionmentioning
confidence: 99%
“…Taking this into account, the present validation results showed that the method described here was comparable concerning sensitivity with published procedures for the measurement in blood,7,13,14 serum,15 and urine,26 but faster and easier to use with regard to sample processing. LC/MS/MS and GC/MS methods developed for the trace determination of CP in urine of hospital workers were more sensitive than the method presented here 21,27. However, these methods required laborious sample preparation including pH adjustment and liquid‐liquid extraction, and only the parent compound and no metabolites were determined.…”
Section: Resultsmentioning
confidence: 93%
“…7 Several environmental wipe sampling studies have demonstrated widespread surface contamination including the outer surface of syringes, drug vials, and preparation and administration areas. [8][9][10][11][12][13][14][15][16][17][18] To limit this exposure and protect health care workers, safe HD-handling guidelines have been incorporated such as a biological safety cabinet (BSC) and personal protective equipment (eg, gloves, gowns, mask). 1,[19][20][21] However, studies show that occupational exposure still occurs despite the use of these protective guidelines.…”
Section: Introductionmentioning
confidence: 99%